Pengaruh Social Capital Dan Entrepreneurial Self-Efficacy Terhadap Entrepreneurial Intention Pada Pengusaha Start Up di Kota Denpasar - I Kadek Surya Wibawa; I Ketut Merta; I Made Anom Arya Pering (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The condition of a person's motivation is based more on what they believe than what is objectively true. Personal perception like this plays an important role in the development of one's intention to become an entrepreneur (Entrepreneurial Intention). This data analysis technique uses quantitative analysis, classical assumption test, correlation analysis, determination analysis, multiple linear regression analysis, and hypothesis testing (F test and t_test). The results of this study, 1) Social capital has a significant positive effect on Entrepreneurial Intention in start-up entrepreneurs. 2) Entrepreneurial Self-Efficacy has a significant positive effect on Entrepreneurial Intention in start-up entrepreneurs. 3) Social capital, Entrepreneurial Self-Efficacy variable simultaneously has a significant effect on Entrepreneurial Intention in start-up entrepreneurs.